Hakikat Supervisi Pendidikan - Hasrul. B; Khusnul Khotimah Mursalim; Rahmawati Rahmawati; Nurul Karimah Ahmad; Maman A Majid Binfas; Cita Audia (Departement of Mathematics Education, 2023)
The purpose of this article is to find out about the nature of educational supervision, the role of supervision, the purpose of supervision, principles of supervision, types (styles) of educational supervision. The research was carried out at the base school of the flagship presidential instruction of Putri Taman Sari. In this study using a descriptive literature method, from various sources, namely books, articles, journals, and other reading sources. The objective of creating this interactive media is to facilitate and simplify the process of delivering educational. The result of the evaluation, namely Education Supervision, is a method carried out by school supervisors or school heads with the aim of improving the quality of learning in each educational institution, and includes various interrelated aspects, such as monitoring, guidance, evaluation, and development of teacher professionalism. With the aim of providing assistance and providing convenience to educators in improving their teaching abilities, it aims to realize the learning goals of students to be achieved.